Temples of India (Ocean books, 2000)
Temple construction in India started nearly 2000 years ago and marked the transition of Hinduism from the Vedic religion. The architecture of Hindu temples has evolved ever since resulting in a great variety of styles. They are usually dedicated to one primary Hindu deity and feature a murti (sacred image) of the deity. Although it is not mandatory for a Hindu to visit a Hindu temple regularly, they play a vital role in Hindu society and culture.